Coordination Resistance in Cross-Functional NPD Projects: The Moderating Role of Temporal Leadership - Zheng, Yujuan; Jiang, James; Huang, Wei Wayne; Wu, Xiaosong; Ren, Haitao (IEEE transactions on engineering management, 2024)
Coordination cost is a critical management issue in cross-functional automotive new product development (NPD) projects, especially in complex environments. However, the literature has neglected to analyze the specific mechanisms by which coordination costs due to complexity may be reduced. This article examines whether and how two dimensions of temporal leadership reduce the coordination cost caused by complexity. In particular, we argue that two dimensions of temporal leadership, namely relationship-oriented and task-oriented temporal leadership, mitigate the effects of complexity on NPD coordination cost through coordination resistance. Based on survey data from 196 automotive NPD project managers, results show that coordination resistance significantly mediates the relationship between complexity and coordination costs. Relationship- and task-oriented temporal leadership also moderate the relationship between different kinds of project complexity and coordination resistance. When the level of relationship-oriented temporal leadership is high, the effect of organizational complexity on coordination resistance weakens. Contrary to our hypotheses, the effect of technological complexity on coordination resistance is stronger when the level of task-oriented temporal leadership is high, suggesting that the project manager should consider different dimensions of temporal leadership when faced with different complexities.